2016
DOI: 10.5664/jcsm.5802
|View full text |Cite
|
Sign up to set email alerts
|

Sleep/Wake Patterns and Parental Perceptions of Sleep in Children Born Preterm

Abstract: Study Objectives:To compare sleep/wake patterns in children born preterm in Australia vs Canada and determine cultural differences in the relationship between parental perception of sleep and actual sleep behaviors. Methods: Australian and Canadian children born preterm were recruited from the Caffeine for Apnea of Prematurity trial (n = 188, 5-12 y) and underwent 14 days actigraphy monitoring. Parents completed the National Sleep Foundation 2004 Sleep in America questionnaire. Cross-cultural differences in sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…We chose SE as the primary outcome, as lower birth weight is associated with lower sleep efficiency (assessed by actigraphy) in children 13 and to replicate a clinically relevant measure as normal spectral EEG values have not been established. Nonetheless, in this study, we did identify significant differences in sleep parameters with our small sample size, which marry to those previously published in preterm children, 34 and therefore, we are confident that our findings are robust.…”
Section: Limitationssupporting
confidence: 89%
See 2 more Smart Citations
“…We chose SE as the primary outcome, as lower birth weight is associated with lower sleep efficiency (assessed by actigraphy) in children 13 and to replicate a clinically relevant measure as normal spectral EEG values have not been established. Nonetheless, in this study, we did identify significant differences in sleep parameters with our small sample size, which marry to those previously published in preterm children, 34 and therefore, we are confident that our findings are robust.…”
Section: Limitationssupporting
confidence: 89%
“…Shorter sleep duration in preterm AGA children has been suggested previously. 34 Using actigraphy studies, children born preterm aged 7-12 averaged 8 hours sleep per night, 1 hour less than population recommendations for their age. 34 Short sleep duration may arise due to altered circadian rhythms in children born preterm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a combined Australian and Canadian study of older children (5–12 years of age) born preterm (∼27 weeks GA, 942–998 g), sleep measured by actigraphy and by parental assessment showed that these children also had a shorter sleep duration, sleeping on average around 8 h (Biggs et al . ), with earlier bed and wake times seen in the Australian children. This is in contrast to the recommended sleep durations of 10–13 h for 5‐year‐olds, 9–11 h for 6–13‐year‐olds (Biggs et al .…”
Section: Introductionmentioning
confidence: 84%
“…Actigraphy is not a direct measurement of sleep, but is a convenient alternative method to determine someone's sleep patterns. There are professional‐level actigraphs that already have been validated in published studies .…”
mentioning
confidence: 99%